Studi Pola Konsumsi Dan Status Gizi Atlet Binaraga Persatuan Angkat Besi Binaraga Dan Angkat Berat Seluruh Indonesia (PABBSI) Madiun Jawa Timur Dalam Persiapan Kejuaraan Daerah Di Madiun Tahun 2013 - Rohma Yuanita; Apoina Kartini; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Food role in bodybuilder of PABBSI Madiun never monitored by KONI and never consultate with medical person. Disbalance betwen practice andfood cosumption cause dehydration in athlete. The objectivethis research is toanalysbetwen food consumption pattern and nutrition needed bodybuilder of PABBSI Madiun in preparation of regional championship. This study use descriptive study in 5 PABBSI’s athlete who will participate in regional championship inMaret atMadiun.The result of this study descripton that average bodybuilder athlete deficite in kalori’s needed, have trend that deficite in kalori’s consumption in 1 month, 1 week and 3 days before competition. Good in vitamin needed, with trend upcrase vitamin consumption. Moderate in mineral needed and deficite in water needed. Tren of consumption water is deficitedecerease before competition. The result of this study also description that average of bodybuilder athlete have good nutrition status during 1 month, 1 week and 3 days before competition. The conclusion of this research is all of bodybuilder athlete get dehydration because of deficite in consumption water. It cause headache and hot in their body